Removal of toxic and heavy metals from Anadara Granosa using chelating agents [electronic resource] - Nurul Hazirah Mukhtar, 1989- (2013)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2013